ANALISIS PENGGUNAAN SISTEM INFORMASI AKUNTANSI PONDOK PESANTREN MODERN AL-HASYIMIYAH DARUL ULUM - Daulay, Yusrina; Juliati Nasution, Yenni Samri; Syafina, Laylan (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2024)
The purpose of this study was to determine the method of recording financial statements at Pondok Pesantren Modern Alhasyimiyah Darul Ulum. Qualitative research is used as a research method. The sources of information used are important information obtained through direct meetings and optional information obtained from related reports. The area of this examination is North Padang Lawas. The phenomena that occur in the school of Modern Islamic Boarding School Alhasyimiyah Darul Ulum have not been by PSAK 45 regulations. The data sources conducted by researchers are interviews, documentation, and observation at Modern Islamic Boarding School Alhasyimiyah Darul Ulum and the techniques used by researchers to collect data are data sorting, data presentation, and data verification. The results of the research at the Modern Islamic Boarding School Alhasyimiyah Darul Ulum are currently not following the bookkeeping data framework plan at the Islamic Living School which is not by PSAK 45, considering that there are still a few financial statement data framework reports that are not made by the pesantren, especially the Money Position Report, Explanation of Income, Notes on Fiscal Summary.